Human Rights Indicators as “Development 2.0”? (Alternautas, 2014)
Are there currently more alternative projects of and to development ongoing in the Latin American region? Others than, for example, Buen Vivir (Ecuador)/Vivir Bien (Bolivia), self-governance, participatory budgeting and a general political rupture through the appearance of, what de la Cadena has called, “Earth-beings” (2010)? In this article, I trace another legal-technical, yet humanist, approach to improve people lives in the region; one that has been termed as 'Development 2.0'. This label points at the fusion of two overlapping, yet partly contradicting businesses and movements: social and econ sciences-related development, on the one hand, and legal and technical human rights, on the other (de Béco, 2014). While for a long time both were promoted somehow separately – by different actors and through different institutions (what de Béco has characterized as rather strictly ‘norm-related’ in the case of human rights and more flexible ‘change-related’ in the case of development) – recent advances and ongoing debates regards post-2015 Millennium Development Goals (MDG) have spurred initiatives toward mutually more integral approaches (e.g. Raza and Baxewanos, 2013).